2001
DOI: 10.1046/j.1365-2559.2001.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle cells and pericytes express MMP‐1, MMP‐9, TIMP‐1 and type I procollagen in inflammatory bowel disease

Abstract: Our results suggest that MMPs are involved in the tissue remodelling, angiogenesis and promotion of leucocyte extravasation in the actively inflamed area in the ulcer base in both UC and CD. MMP-1 expression in the mucosa may be related to the initial step of ulceration in UC. Therapeutic manipulation of extracellular matrix turnover would be an effective therapy to alleviate active inflammation and accelerate ulcer healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 33 publications
8
68
0
2
Order By: Relevance
“…Interestingly, in a recent study, Spurbeck et al (53) demonstrated that forced expression of tissue inhibitor of metalloproteinase-3 in murine neuroblastoma and melanoma tumors resulted in an unanticipated increase in the number of PECAM/CD31-positive endothelial cells but a decreased pericyte recruitment. In additional support for a role of MMP-9 in pericyte recruitment is the observation that MMP-9 expression is localized to the perivascular smooth muscle cells and pericytes at the proliferating borders of human glioma (54) and in pericytes of venules in ulcerative bowel disease (55). Accordingly, we observed a strong expression of MMP-9 in vascular and perivascular cells in neuroblastoma tumors.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, in a recent study, Spurbeck et al (53) demonstrated that forced expression of tissue inhibitor of metalloproteinase-3 in murine neuroblastoma and melanoma tumors resulted in an unanticipated increase in the number of PECAM/CD31-positive endothelial cells but a decreased pericyte recruitment. In additional support for a role of MMP-9 in pericyte recruitment is the observation that MMP-9 expression is localized to the perivascular smooth muscle cells and pericytes at the proliferating borders of human glioma (54) and in pericytes of venules in ulcerative bowel disease (55). Accordingly, we observed a strong expression of MMP-9 in vascular and perivascular cells in neuroblastoma tumors.…”
Section: Discussionsupporting
confidence: 69%
“…This increase correlated with an increase in Vegf-B expression. We also observed that MMP-9 localized to both the smooth muscle as reported previously 36 and to sites around tumor vasculature (Fig. 5A).…”
Section: Discussionsupporting
confidence: 88%
“…Systemic sclerosis is characterized by a dysregulation of angiogenesis, which leads to failure to replace damaged vessels with a consequent clinical manifestation of ulcers (33,34). Ulcer formation involves an EcM degradation by different MMPs, which appears to be important not only for the maintenance and progression of inflammation, but also for the repair processes of ulcers (35). Interestingly, our results seem to correlate with those of Hulkkonen et al (36), who found that the MMP-9 -1562 C/T polymorphism, seemed to protect primary Sjogren's syndrome patients from Raynaud's phenomenon.…”
Section: Discussionsupporting
confidence: 81%